Global citrus root microbiota unravels assembly cues and core members - Lombardo, Monia F.; Zhang, Yunzeng; Xu, Jin; Trivedi, Pankaj; Zhang, Pengfan; Riera, Nadia; Li, Lei; Wang, Yayu; Liu, Xin; Fan, Guangyi; Tang, Jiliang; Coletta-Filho, Helvécio D.; et al. (Frontiers in Microbiology, 2024)
Introduction Citrus is one of the most important fruit crops worldwide, and the root-associated microbiota can have a profound impact on tree health and growth. Methods In a collaborative effort, the International Citrus Microbiome Consortium investigated the global citrus root microbiota with samples collected from nine citrus-producing countries across six continents. We analyzed 16S rDNA and ITS2 amplicon sequencing data to identify predominant prokaryotic and fungal taxa in citrus root samples. Comparative analyses were conducted between root-associated microbial communities and those from the corresponding rhizosphere and bulk soil samples. Additionally, genotype-based group-wise comparisons were performed to assess the impact of citrus genotype on root microbiota composition. Results Ten predominant prokaryotic phyla, containing nine bacterial phyla including Proteobacteria, Actinobacteria, Acidobacteria, and Bacteroidetes and one archaeal phylum (Thaumarchaeota), and multiple fungal phyla including Ascomycota and Basidiomycota were identified in the citrus root samples. Compared with the microbial communities from the corresponding rhizosphere and bulk soil samples from the same trees, the prokaryotic and fungal communities in the roots exhibited lower diversity and complexity but greater modularity compared to those in the rhizosphere. In total, 30 root-enriched and 150 root-depleted genera in bacterial community were identified, whereas 21 fungal genera were enriched, and 147 fungal genera were depleted in the root niche compared with the rhizosphere. The citrus genotype significantly affected the root prokaryotic and fungal communities. In addition, we have identified the core root prokaryotic genera comprising Acidibacter, Allorhizobium, Bradyrhizobium, Chitinophaga, Cupriavidus, Devosia, Dongia, Niastella, Pseudomonas, Sphingobium, Steroidobacter and Streptomyces, and the core fungal genera including Acrocalymma, Cladosporium, Fusarium, Gibberella, Mortierella, Neocosmospora and Volutella. The potential functions of these core genera of root microbiota were predicted. Conclusion Overall, this study provides new insights into the assembly of microbial communities and identifies core members of citrus root microbiota across a wide geographic range. The findings offer valuable information for manipulating root microbiota to enhance plant growth and health.